Identification of hexose kinase genes in Kluyveromyces marxianus and thermo-tolerant one step producing glucose-free fructose strain construction - Zhang, Guorong (Sci Rep, 2017)
In yeast, the hexose assimilation is started at hexose phosphorylation. However, in Kluyveromyces marxianus, the hexokinase (HXK) and glucokinase (GLK) genes were not identified by experiments. Meanwhile, the glucose-free fructose product requires more cost-efficient method. In this study, the KmHXK1 and KmGLK1 genes were functionally identified through gene disruption, over-expression and recombinant enzymes characterization. Both glucose and fructose assimilation ability decreased significantly in KmHXK1 disrupted strain YLM001, however, this ability was not changed obviously in KmGLK1 disrupted strain YLM002. When over-expressing KmGLK1 in YLM001, only the glucose assimilation ability was recovered in obtained strain (YLM005). The kinetic constant analysis of recombinant enzymes also proved that KmHXK1 could phosphorylate glucose (Vmax 553.01 U/mg, Km 0.83 mM) and fructose (Vmax 609.82 U/mg, Km 0.52 mM), and KmGLK1 only phosphorylate glucose with a Vmax of 0.73 U/mg and a Km 4.09 mM. A thermo-tolerant strain YGR003 which produced glucose-free fructose from Jerusalem artichoke tuber in one step was constructed based on the obtained information. The highest production and fastest productivity were 234.44 g/L and 10.26 g/L/h, respectively, which were several folds of the results in previous reports.